STUDY OF THE INFLUENCE OF EXTERNAL ECONOMIC FACTORS ON THE STRUCTURE OF THE REGIONAL TOURISM INDUSTRY ON THE EXAMPLE OF THE NORTH CAUCASUS - A. V. Baturov; V. F. Kshishnevskaya (Современная наука и инновации)
The article is devoted to the study of the stability of the local market of the hospitality industry in conditions of varying degrees of covid restrictions and the level of vaccination in the regions of the world, escalation of military conflicts, rising prices for energy and raw materials, problems with logistics chains. External negative factors have changed the structure of demand for services in general and tourist services in particular. This trend is based on the budget, individual segment of domestic tourism, taking into account sanitary and epidemiological restrictions. There is a growing demand for cheap tours, "micro tours" and destinations (not far from home). Transport accessibility becomes an important factor reducing the demand for travel services. The resort regions of the North Caucasus (Caucasian Mineral Waters) are in an advantageous position in this direction, as they have a developed recreational infrastructure and qualified personnel.